Implementasi Nilai-nilai Islam untuk Mendapatkan Nasabah yang Loyal dalam BMT Mandiri Sejahtera Cabang Dukun - Hadi Siswo; M. Fathor Rohman; Ainur Rofiq (Al-Muzdahir : Jurnal Ekonomi Syariah, 2019)
The Sharia Financial Services Cooperative (KJKS) Baitul Mal Wat Tamwil (BMT) Mandiri Sejahtera Karangcangkring Dukun Branch is a growing financial services company that requires efforts to develop one of them through customer loyalty in order to gain the trust of customers, so that with the existence of customers who loyally participate in advancing BMT Mandiri Sejahtera Karangcangkring Dukun Branch with the formulation of How to apply Islamic Values ​​at BMT Mandiri Sejahtera Karangcangkring East Java Branch Dukun Gresik in getting loyal customers and how the strategy of BMT Mandiri Sejahtera Dukun Branch in getting loyal customers. This research is a qualitative research that uses empirical methods. Qualitative research is research in the form of words or not numbers, even if there are numbers, they are supporting. While the empirical method is research that aims to reveal the reality in the field by taking data based on the experience of respondents, where the law is seen as a fact because the law will interact with other social institutions. The purpose of analyzing these two things is to make a description of one object according to the facts so that BMT Mandiri Sejahtera Karangcangkring East Java Branch of Dukun Gresik can get loyal customers in accordance with Islamic values. And the instruments of this research are interviews, observations, literature studies and questionnaires.